2016
DOI: 10.1038/srep38036
|View full text |Cite
|
Sign up to set email alerts
|

The invasive stoloniferous clonal plant Alternanthera philoxeroides outperforms its co-occurring non-invasive functional counterparts in heterogeneous soil environments – invasion implications

Abstract: Environmental heterogeneity is considered to play a defining role in promoting invasion success, and it favours clonal plants. Although clonality has been demonstrated to be correlated with the invasion success of several species of clonal invasive plants in heterogeneous environments, little is known about how the spatial scale of heterogeneity affects their performance. In addition, the factors that distinguish invasive from non-invasive clonal species and that enhance the invasive potential of clonal exotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
2
14
1
Order By: Relevance
“…Density‐dependent effects have different influences on germination. For example, high densities restricted the subsequent seed germination of desert annuals, ramet establishment increased with seed density, or density did not affect the seed germination or ramet establishment . The results showed that higher fleshy root densities significantly restricted the sprouting and growth of A. philoxeroides , which was consistent with previous studies on propagules of other species .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Density‐dependent effects have different influences on germination. For example, high densities restricted the subsequent seed germination of desert annuals, ramet establishment increased with seed density, or density did not affect the seed germination or ramet establishment . The results showed that higher fleshy root densities significantly restricted the sprouting and growth of A. philoxeroides , which was consistent with previous studies on propagules of other species .…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, compared with non‐clonal plants, clonal plants generally show positive responses to heterogeneity in terms of overall growth, and they display a greater number of morphological features, tend to efficiently capture resources and further increase their local growth in heterogeneous environments . However, ramet growth traits were not affected by soil heterogeneity, and this result was consistent with a previous study showing that the growth of fragments of A. philoxeroides benefited less from soil heterogeneity . The results were inconsistent with a previous study that soil heterogeneity can increase the growth performance of fragments of A. philoxeroides .…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Therefore, B. yagara was more sensitive to soil nutrient heterogeneity than to heterogeneity of water supply. Spatial or temporal heterogeneity in soil nutrient distribution and water supply patterns may be highly important with respect to the growth performance and population structure of clonal plants (Hutchings et al, 2003; Wang T. et al, 2016; Wang Y.J. et al, 2016; You et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the long-term response of Holcus lanatus was to produce far less shoot biomass in the heterogeneous treatment than expected under the homogeneity treatment (Fransen and Kroon, 2001). In addition, the growth performance of clonal plants in heterogeneous soil conditions may be correlated with the spatial scale of heterogeneity (Wijesinghe and Hutchings, 1997; Wang et al, 2016). For example, the growth of Glechoma hederacea was dependent on the spatial scale of soil nutrient heterogeneity (Wijesinghe and Hutchings, 1997), but Alternanthera philoxeroides displayed generally similar, scale-independent performance in most traits under different scales of soil nutrient heterogeneity (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%